Sosialisasi Mutu Pelayanan Pasien Rawat Jalan di Rumah Sakit Paru Manguharjo Madium - Asmirati Yakob; Lina Alfiyani; Anindita Hasniahti Rahmah; Widya Kaharani Putri; Nurul Fatimah; Avi Arya Buana Jaya Putra; Kristofara Karolina Kewa (Yayasan Habiburrahman Jamalu Bina Ummat, 2024)
Satisfaction in services contained in a hospital can be measured by the quality of its health workers. High-quality health services are able to provide satisfaction to health service users at the standard level of satisfaction and code of ethics of a profession. Continuous improvement can be done through a process that is carried out on the quality of health services to meet all customer expectations. The purpose of this activity is to socialize the quality of outpatient services at Manguharjo Madiun Lung Hospital. The results of this PKM socialization showed that respondents who stated that they were satisfied with the quality of officer service because officers had the ability/reliability and experience in carrying out medical actions. This shows that the better the service provided by officers to patients related to the actions given, and can provide clear information related to the disease and the actions to be taken, the customer/patient will feel more satisfied with the service received. In order to better understand and understand how the quality of service in the hospital, especially outpatient, is in accordance with the patient's expectations with the reality felt during the examination. So it is important to provide this education to patients so that they are a little educated and not easily consumed by hoaxes about the issue of poor service.